Polit-ökonomische Aspekte des Berichts zur Lage der Verbraucher:innen; Political-economic aspects of the report on the position of consumers by the Advisory Council for Consumer Affairs (SVRV) - Gert G. Wagner (Wirtschaftsdienst, 2021)
Der Sachverständigenrat für Verbraucherfragen hat erstmals ein breit angelegtes Gutachten zur Lage der Verbraucher:innen in Deutschland vorgelegt. Gert G. Wagner, Mitglied im Sachverständigenrat für Verbraucherfragen, stellt aus seiner persönlichen Sicht ausgewählte Analysen, Ergebnisse und Empfehlungen vor. Über das Gutachten hinausgehend wird auch auf relevante Ereignisse hingewiesen, die nach Abschluss des Gutachtens stattfanden: die Vorlage des EU-Verordnungsvorschlags "Artificial Intelligence Act", das Klimaschutz-Urteil des Bundesverfassungsgerichts und der Gesetzentwurf zum autonomen Fahren. – – For the first time, the German Advisory Council for Consumer Affairs (SVRV) has published a comprehensive report on the position of consumers in Germany. The author, who is a member of the SVRV, presents selected analyses, results and recommendations. Additionally, relevant events that have taken place after the report was completed are also mentioned: the presentation of the proposed EU regulation "Artificial Intelligence Act", the climate protection ruling of the Federal Constitutional Court and the draft law on autonomous driving in Germany.
Keywords: A12; A29; D11; D12; D18; D31; D82; L66; O18; Q18; Q56; R41; 330